2005
DOI: 10.2511/rpsd.30.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mediated Conversational Repair in Students with Moderate and Severe Disabilities

Abstract: Conversation skills are critical to learning and the development of social relationships. Some students with severe disabilities have a difficult time conversing with their nondisabled classmates because of their unintelligible verbalizations or an inability to correct or repair a message that may have been misunderstood by their conversational partner. For intervention purposes, extant literature strongly suggests that typical similar-age peers are effective change agents. In a study using a multiple baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…These data indicates that while activity engagement together with students with SMD did not differ between peer tutors and APE teachers, peer tutors tended to provide more frequent instructions as teachers did. Several studies in special education have indicated importance of the frequent prompt delivery strategies to foster a higher level of on-task behavior and correct task responding in persons with severe and multiple disabilities (e.g., Lancioni, Dijkstra, O'Reilly, Groeneweg & van den Hof, 2000;Lancioni, Dijkstra, O'Reilly, Brower, Groeneweg, Bikker, Flameling, & van den Hof, 2001;Weiner, 2005). Unfortunately, in APE research investigations addressing prompt frequency to change behaviors of students with SMD has been minimal.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicates that while activity engagement together with students with SMD did not differ between peer tutors and APE teachers, peer tutors tended to provide more frequent instructions as teachers did. Several studies in special education have indicated importance of the frequent prompt delivery strategies to foster a higher level of on-task behavior and correct task responding in persons with severe and multiple disabilities (e.g., Lancioni, Dijkstra, O'Reilly, Groeneweg & van den Hof, 2000;Lancioni, Dijkstra, O'Reilly, Brower, Groeneweg, Bikker, Flameling, & van den Hof, 2001;Weiner, 2005). Unfortunately, in APE research investigations addressing prompt frequency to change behaviors of students with SMD has been minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies focused on the types of prompts (e.g., echoic, tact, textual) used to directly teach a vocal response to a vocal stimulus (Ingvarsson & Le, 2011;Kisamore, Karsten, Mann, & Conde, 2013). Others examined specific reinforcement procedures (Mason, David, & Andrew, 2015) and peer-mediated behavioral skills training (Beaulieu, Hanley, & Santiago, 2014;Weiner, 2005).…”
Section: Research Emphasismentioning
confidence: 99%
“…For example, Polick and colleagues showed that providing descriptive praise (i.e., saying BGreat job saying ___^) was more effective in teaching intraverbal behavior to young children with autism than general praise (i.e., saying BGreat job^). Finally, peer-mediated behavioral skills training has been shown to increase appropriate complex intraverbal skills in the form of conversations (Beaulieu et al, 2014) and to improve unintelligible vocalizations which ultimately lead to longer intraverbal exchanges (Weiner, 2005) with children with moderate to severe developmental disabilities. The current literature suggests that no single prompt type is always superior when teaching the intraverbal.…”
Section: Research Emphasismentioning
confidence: 99%
“…Considering the variety and complexity of stimuli controlling verbal behavior, learning appropriate verbal exchanges can be a daunting task for individuals with autism and other developmental disabilities (e.g., Finkel and Williams 2001;Sundberg and Sundberg 2011;Taylor and Harris 1995;Weiner 2005). Thus, interventions designed to increase intraverbal repertoires and promote generalization to untrained verbal relations seem like a worthwhile effort, as it would be prohibitive to teach children with autism all the potential intraverbal responses required for advanced verbal exchanges.…”
Section: Discussionmentioning
confidence: 99%